2016
DOI: 10.1021/acs.jproteome.6b00538
|View full text |Cite
|
Sign up to set email alerts
|

GC–MS Metabolomics Identifies Metabolite Alterations That Precede Subclinical Mastitis in the Blood of Transition Dairy Cows

Abstract: The objectives of this study were to determine alterations in the serum metabolites related to amino acid (AA), carbohydrate, and lipid metabolism in transition dairy cows before diagnosis of subclinical mastitis (SCM), during, and after diagnosis of disease. A subclinical mastitis case was determined as a cow having somatic cell count (SCC) > 200 000/mL of milk for two or more consecutive reports. Blood samples were collected from 100 Holstein dairy cows at five time points at -8 and -4 weeks before parturiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 49 publications
8
56
0
Order By: Relevance
“…In fact, mastitis has been shown to decrease reproductive parameters including conception rate 33 . Using metabolomics, a recent study compared the plasma metabolomic profiles between dairy cows with subclinical mastitis and healthy control cows 34 . They identified 17 metabolites, with good predictive abilities, altered in the subclinical population during the week of diagnosis including valine, serine, tyrosine, and phenylalanine 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, mastitis has been shown to decrease reproductive parameters including conception rate 33 . Using metabolomics, a recent study compared the plasma metabolomic profiles between dairy cows with subclinical mastitis and healthy control cows 34 . They identified 17 metabolites, with good predictive abilities, altered in the subclinical population during the week of diagnosis including valine, serine, tyrosine, and phenylalanine 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Using metabolomics, a recent study compared the plasma metabolomic profiles between dairy cows with subclinical mastitis and healthy control cows 34 . They identified 17 metabolites, with good predictive abilities, altered in the subclinical population during the week of diagnosis including valine, serine, tyrosine, and phenylalanine 34 . In a companion study they found that cattle with subclinical mastitis had greater serum concentrations of the proinflammatory cytokine TNFα 35 , suggesting the initiation of systemic infection preceding clinical mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…The SCC of raw milk was measured using a laser beam Bentley FTS/FCM400 Combi Instrument (Chaska, MN, United States). A threshold of 200,000 cells/mL is indicative of subclinical mastitis ( Dervishi et al, 2016 ). Eleven cows used in this study were diagnosed with subclinical mastitis because the SCC in a majority of milk samples was ≥200,000 cells/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the association between difference in gene expression and incidence and progression of ketosis remains unknown. The 'Omics' technologies of transcriptomics, metabolomics, and proteomics have increasingly been used to investigate the underlying molecular mechanism of complex diseases in cattle, such as hyperthermic stress [21], mastitis [22], footrot [23], and lipid metabolome disorder [24]. In these studies, whole blood has been widely used due to convenient and non-invasive sampling.…”
Section: Introductionmentioning
confidence: 99%